Evaluation of the Pivot Profile©, a new method to characterize a large variety of a single product: Case study on honeys from around the world. (April 2018) - Deneulin, Pascale; Reverdy, Caroline; Rébénaque, Pierrick; Danthe, Eve; Mulhauser, Blaise
Abstract: Honey is a natural product with very diverse sensory attributes that are influenced by the flower source, the bee species, the geographic origin, the treatments and conditions during storage. This study aimed at describing 50 honeys from diverse flower sources in different continents and islands, stored under various conditions. Many articles have been published on the sensory characterization of honeys, thus a common list of attributes has been established, but it appeared to be poorly suited to describe a large number of honeys from around the world. This is why the novel and rapid sensory evaluation method, the Pivot Profile©, was tested, with the participation of 15 panelists during five sessions. The first objective was to obtain a sensory description of the 50 honeys that were tested. From 1152 distinct terms, a list of 29 sensory attributes was established and the attributes divided into three categories: color/texture (8 terms), aroma (16 terms), and taste (5 terms). At first, the honeys have been ranked according to their level of crystallization from fluid/liquid to viscous/hard. Then color was the second assessment factor of the variability. In terms of aroma, honeys from Africa were characterized by smoky, resin, caramel and dried fruit as opposed to floral and fruity, mainly for honeys from South America and Europe. Finally, the honeys were ranked according to their sweetness. The second objective of this study was to test the new sensory method, called Pivot Profile© which is used to describe a large number of products with interpretable results. Graphical abstract: Image 1 Highlights: 50 honeys from around the world were characterized by the Pivot Profile© method during 5 sessions. Honeys from Africa stood out with their stronger aroma and dark color. Pivot Profile© appeared to be an interesting method for a large variety of product. More investigations in regard of vocabulary used in and between sessions have been suggested.